Three new species of the genus Anacronicta Warren in Seitz, 1909 (Noctuidae: Pantheinae) from northeast India - Irungbam, Jatishwor Singh; Fric, Zdenek Faltynek (Zootaxa, 2025)
Three new species, Anacronicta pseudonitida Irungbam & Fric, sp. nov., A. albicans Irungbam & Fric, sp. nov., and A. manipura Irungbam & Fric, sp. nov., are described from Manipur (North-East India). Another species, A. albargentea Speidel & Kononenko, 1998, is reported for the first time from North-East India (Manipur and Arunachal Pradesh). Illustrations of the habitus, male genitalia and phylogenetic tree are provided. A global checklist of the genus Anacronicta is presented herewith.